Combined influence of supercharging, EGR, biodiesel and ethanol on emissions of a diesel engine: Proposal of an optimization strategy. (15th September 2020) - Ayhan, Vezir; Çangal, Çiçek; Cesur, İdris; Safa, Aykut
Abstract: There are several abatement technologies used for emissions, especially NOx emissions, from Diesel engines. Exhaust Gas Recirculation (EGR) system and alternative blend fuels are leading among the common methods used. Although the EGR provides remarkable reduction in NOx emissions, has negative effects on other emissions and engine performance. Among the alternative fuels, biodiesel and ethanol are preferred for being renewable. Chemical properties make these fuels feasible to be used in diesel blends at various ratios. Utilizing these fuels with diesel fuel in blends on engines provide improvements in engine performance parameters and emissions characteristics. However, biodiesels with oxygen content increase NOx emissions in particular. Eventually, utilizing different methods together is beneficial to optimize for the most convenient utilization ratios and conditions regarding all the emissions from engine. In this study, utilizing supercharging, EGR, biodiesel at various ratios and introducing ethanol fumigation through intake manifold of a DI diesel, and the most convenient engine operation conditions and ratios of the factors are determined through optimization using Taguchi method regarding engine brake specific heat consumption and emissions. Experiments are conducted regarding to orthogonal series L16 (4 2  × 2 2 ) with the combinations of factor and levels. Effect degrees of factors are determined through variation analysis. As a conclusion, factors evaluated in combination under different engine operating conditions, and factors and levels minimizing brake specific heat consumption and emissions, NO, smoke, HC, CO and CO2, are stated. Highlights: Taguchi method was applied to investigate factors affecting emissions. The L16 orthogonal series was used in engine testing. Direct injection diesel engine was used for the experiments. Studies were done by Taguchi method, saving 70% in terms of time and cost.